2021
DOI: 10.1111/1754-9485.13359
|View full text |Cite
|
Sign up to set email alerts
|

Head and neck cancers: Monitoring quality and reporting outcomes

Abstract: Introduction Head and neck cancers (HNC) require high level multidisciplinary care to achieve optimal outcomes. Reporting of quality indicators (QIs) has been instigated by some health services in an effort to improve quality of care. The aim of this study was to determine the quality of care provided to patients with HNC at a single institution by analysing compliance with QIs and to explore the feasibility and utility of collecting this data. Methods This was a single institution retrospective chart review o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…This study follows an earlier study that reported quality indicators in head and neck cancer and identified time to PORT as an area for improvement at our institution. 16 Ethics approval for this study was granted by the Institutional Human Research Ethics Committee (HREC/QTHS/67801).…”
Section: Methodsmentioning
confidence: 99%
“…This study follows an earlier study that reported quality indicators in head and neck cancer and identified time to PORT as an area for improvement at our institution. 16 Ethics approval for this study was granted by the Institutional Human Research Ethics Committee (HREC/QTHS/67801).…”
Section: Methodsmentioning
confidence: 99%